Relationships between sprinting, agility, and jump ability in female athletes - Vescovi, J. D.; McGuigan, M. R. (Journal of Sports Sciences, 2008)
The aim of this study was to assess the relationships between various field tests in female athletes. Altogether, 83 high school soccer, 51 college soccer, and 79 college lacrosse athletes completed tests for linear sprinting, countermovement jump, and agility in a single session. Linear sprints (9.1, 18.3, 27.4, and 36.6 m) and agility tests (Illinois and pro-agility) were evaluated using infrared timing gates, while countermovement jump height was assessed using an electronic timing mat. Pearson's product - moment correlation coefficients (r) were used to determine the strength and directionality of the relationship between tests and coefficients of determination (r2) were used to examine the amount of explained variance between tests. All of the performance scores were statistically correlated with each other; however, the coefficients of determination were low, moderate, and high depending on the test pairing. Linear sprint split times were strongly correlated with each other (r = 0.775 to 0.991). The relationship between countermovement jump height and linear sprinting was stronger with the longer distances (27.4 and 36.6 m) than with the shorter distances (9.1 and 18.3 m), and showed a stronger relationship within the college athletes (r = -0.658 to -0.788) than high school soccer players (r = -0.491 to -0.580). The Illinois and pro-agility tests were correlated (r 0.600) with each other as well as with linear sprint times. The results of this study indicate that linear sprinting, agility, and vertical jumping are independent locomotor skills and suggest a variety of tests ought to be included in an assessment protocol for high school and college female athletes.